Synthesis and rac-lactide ring-opening polymerisation studies of new alkaline earth tetrahydroborate complexes. - Collins, R; Unruangsri, J; Mountford, P (2013)
Reaction of K[HC(C(Me)NAr')(2)] (Ar' = 2,6-C(6)H(3)(i)Pr(2)) with Mg(BH(4))(2) afforded the pseudo four-coordinate tetrahydroborate complex Mg{HC(C(Me)NAr')(2)}(BH(4))(THF) (1). The corresponding reaction of Ca(BH(4))(2)(THF)(2) or Sr(BH(4))(2)(THF)(2) gave the pseudo five-coordinate analogues M{HC(C(Me)NAr')(2)}(BH(4))(THF)(2) (M = Ca (2) or Sr (3)). All three compounds 1-3 have been structurally characterised. According to X-ray crystallography and IR spectroscopy all possess κ(3)-bound BH(4) ligands in the solid state. This coordination mode is also maintained in THF solution for 2 and 3, whereas complex 1 appears to form a bis(THF) complex containing a κ(2)-bound BH(4). Reaction of 1 with K[HC(P(Ph(2))NAr')(2)](THF)(2) formed Mg{HC(P(Ph(2))NAr')(2)}(BH(4))(THF)(2) (4) possessing a κ(3)-bound BH(4) ligand in both the solid state and solution. Compounds 1, 2 and 4 are highly active for the ring-opening polymerisation of ε-caprolactone forming dihydroxytelechelic PCL. Compound 1 is also extremely active for the ROP of rac-lactide forming highly heterotactic PLA with good agreement between predicted and measured M(n), in accord with previous studies of alkoxide and amide initiators based on this metal and ligand class. Compounds 2 and 4 were less productive and gave PLA with poorer control of M(n) and negligible heterotactic enrichment. MALDI-ToF MS analysis of the PLA formed with all three catalysts showed a mixture of both -CH(Me)CHO and -CH(Me)CH(2)OH termini arising from the M-BH(4) initiating groups.